Development Content Learning System (CLS) Material Inter-Molecular Force Based on Project Base Learning (PjBL) with Flipped Classrooms in Senior High School - Wimbi Apriwanda; Amalia Putri Lubis; Dini Liya Meirani; Elsa Karolina; Yasinta Ayuningdyah (INTERNATIONAL JOURNAL OF HIGH INFORMATION, COMPUTERIZATION, ENGINEERING AND APPLIED SCIENCE (JHICE), 2021)
E-learning is based on project-based learning with the approach of flipping the class on intermolecular forces as a variant of the learning media. This study aims to produce intermolecular learning material based on project-based learning models and is supported by the zainulteam.id LMS model and to reveal the validity and practicality of E-learning. This type of research is R&D with a 4-D model which includes stages, design, development, and dissemination. This research is in the development stage in the development section of the validity and practicality test. The instruments used were a valid questionnaire given to three experts and a practical questionnaire given to 20 students of SMAN 8 Padang. The data analysis technique used the Aiken V formula and the Kunandar formula. Data analysis shows the content and structure validity of 0.83 and 0.89 and a practical value of 0.83, so that it can prove that the content of e-learning developed is valid and practical